2021
DOI: 10.3390/agronomy11091879
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter and Mineral Composition of Silicate Soils: FTIR Comparison Study by Photoacoustic, Diffuse Reflectance, and Attenuated Total Reflection Modalities

Abstract: This study aims to compare photoacoustic (FTIR–PAS), diffuse reflectance (DRIFT), and attenuated total reflection (ATR) FTIR modalities in the wide wavenumber range from NIR (7500 cm−1) to FIR (150 cm−1) for the same silicate soil samples under the same conditions. The possibilities of non-destructive rapid qualitative analysis of soils by these modalities without comprehensive data treatment were compared. The assignment of more than 100 bands for the chernozem and sod-podzolic as common types of silicate typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 141 publications
1
58
0
5
Order By: Relevance
“…In the case of sample C, the peak at 1794 cm −1 may be regarded as the combination band of υ 1 + υ 4 of carbonate ion [ 23 ]. The absorption band at 697 cm −1 in all tested materials can represent Si-O-Si stretching vibrations [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of sample C, the peak at 1794 cm −1 may be regarded as the combination band of υ 1 + υ 4 of carbonate ion [ 23 ]. The absorption band at 697 cm −1 in all tested materials can represent Si-O-Si stretching vibrations [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band at 697 cm −1 in all tested materials can represent Si-O-Si stretching vibrations [24].…”
Section: The Characterization Of Functional Groupsmentioning
confidence: 95%
“…The reason for this was the very low TOC and BC concentrations in non‐RCH soils , which failed to produce a strong enough signal in the spectra. The PLSR regression coefficients for the RCH soil model (Figure 6) suggested that higher BPCA‐C concentrations coincided with higher carboxyl C=O absorptions at 1732 cm −1 , aromatic C=C absorptions from ionised carboxyl (COO − ) groups or C=O absorptions at 1616 cm −1 (Rebollo et al, 2008; Volkov et al, 2021), aromatic C‐H vibrations at 3000–3100 cm −1 and lower absorptions at the aliphatic CH region at 2800–3000 cm −1 and aromatic C=C stretches associated with lignin at 1518 cm −1 (Ferrari et al, 2011; Volkov et al, 2021; White et al, 2011). Thereby, the coefficients show that BPCA‐C concentrations correlated mainly positive with wavenumber regions associated with charcoal contents in soils.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4d, false-colour FPA The presence of thick layers of soil enveloping the wood of sample #2 together with diffuse mineral grains were clearly observed in the SEM images (Figure 3c). SEM-EDX spectrum (Figure 3d, wood sample #1) shows the presence of very high amount of Ca, Cl, and Si and lower amounts of Na, Mg, Al, S, K, Pb, and Fe; this might be attributed to the penetration of soil components inside the wood, as these elements are the main soil constituents [62].…”
Section: Soil Characterisation and Its Interaction With Ancient Woodmentioning
confidence: 99%